Do Islamic banks more stable than conventional banks? Evidence from Indonesia - Rahmatina A Kasri; Chairilisa Azzahra (Jurnal Ekonomi & Keuangan Islam, 2020)
Purpose – Albeit Islamic banks are often considered more stable than conventional banks, empirical evidence to support the stability view is relatively scanty. This study, therefore, mainly aims to investigate whether Islamic banks are more stable than conventional banks in Indonesia. To enrich and support the analysis, it will also compare the factors influencing the stability of Islamic banks and conventional banks in the country.Methodology – This paper employs a dynamic panel data model using the system-GMM (General Method of Moment) estimator. The data used are quarterly data from 83 conventional banks and 11 Islamic banks in Indonesia during September 2015-June 2019 period. Findings – The study did not find any significant difference in the stability of conventional and Islamic banks. This result is presumably influenced by the small size and small market share of Islamic banks, as well as many similarities between the two types of banking systems. Furthermore, the stability of the conventional bank in Indonesia is more influenced by macroeconomic factors including interest rate, exchange rate and financial inclusions, meanwhile the stability of Islamic banks is more influenced by the banks’ specific factors such as financing growth, efficiency and risk management factors.Research limitations – The data used in the study is limited to the period from September 2015 to June 2019. The variables utilized are also limited to those taken from publicly available financial statements.Originality – This paper provides additional empirical evidence regarding Islamic banking stability in Indonesia by using the latest data. While theoretically Islamic banks are expected to be more stable than conventional banks, this study did not find strong support for the case of Indonesia during the period of observation.